Nutrition, Neuroinflammation and Cognition - Vaidya, Neha; Mandalika, Subhadra (Journal of Nutritional Therapeutics, 2015)
Activation of microglia and astrocytes leads to the production of cytokines and other inflammatory mediators which may contribute to the apoptotic cell death of neurons observed in many neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease. Vulnerability of the central nervous system (CNS) to oxidative and inflammatory stress increases with age and has been postulated to be a leading contributing factor to the cognitive impairment and thereby development of neurodegenerative diseases. Suppression of microglial production of neurotoxic mediators may result in neuroprotection. This heightens the interest in the development of neuroinflammation-targeted therapeutics. Nutrition is involved in the pathogenesis of age-related cognitive decline and also neurodegenerative diseases. Certain nutrients facilitate human brain function with their immediate and long term effects. On the other hand, malnutrition influences the brain throughout life, with profound implications on cognitive decline and dementia. Several phytochemicals with potent antioxidant and anti-inflammatory activities, have been shown to repress microglial activation and exert neuroprotective effects. Thus this review highlights the role of foods, nutrients and phytochemicals in suppressing neuro-inflammation and also enhancing cognition.